Internal auditing in metaverse world: between the prospects of virtual reality and the possibilities of augmented reality - Mohamed Kais Adel Al Gnbri (Universitas Hayam Wuruk Perbanas, 2022)
The research aimed to anticipate the reality of internal auditing under the world of Metaverse, and focused on the two most important technologies in this world, namely: virtual reality and augmented reality. To achieve this goal, this study adopted the normative approach. The added value of the research is it is the first scientific research to link the internal audit with the world of the Metaverse. The most notable findings are: The implications of the Metaverse on internal auditing will be in two directions: The first direction: virtual reality and augmented reality devices will be used in performing the internal audit process on virtual economic activities and business in the Metaverse world, which requires updating and developing some audit methodologies and methods, and the second direction: that the audit The internal audit examines and confirms the Metaverse technology itself, which requires additional audit tasks, and no matter how quickly these two trends move, it can be argued that both necessitate an expansion of the range of services provided by internal audit.